The effect of gender on vastus medialis oblique/vastus lateralis activation ratio during weight and non-weight bearing activities in recreationally subjects - Alaa Abd El Rheem Mohamed; Marwan Mahmoud Aljohani; Yasir Saad Alshehri; Amr Almaz Abdel Aziem; Osama Ahmed Khaled (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate the effect of gender on the activation ratio of vastus medialis oblique to vastus lateralis during straight leg raising and stepdown activities. Method: The cross-sectional study was conducted at the College of Medical Rehabilitation Sciences, Taibah University, Medina, Kingdom of Saudi Arabia, from September 2021 to March 2022, and comprised recreationally active subjects without knee pathology who were distributed in 2 gender-based groups. All the participants were subjected to straight leg raising and stepdown activities thrice and the average value of each activity was noted. The vastus medialis oblique and vastus lateralis electromyographic activity of the dominant limb was recorded using surface electromyography during the activities. The normalised value of the activation ratio of vastus medialis oblique to vastus lateralis levels was calculated. Data was analysed using SPSS 25. Results: Of the 60 subjects, there were 30(50%) males with mean age 30.00±5.91 years, mean height 167±5.63cm, mean body weight 66.76±6.14kg, and mean body mass index 23.97±3.02kg/m2. There were 30(50%) females with mean age 29.03±5.34 years, mean height 186±6.20cm, mean body weight 68.5±5.6 kg and mean body mass index 23.76±3.22 kg/m2. There was no significant difference in the normalized electromyography activities of the vastus medialis oblique and vastus lateralis muscles between males and females (p>0.05). Also, no significant difference was found in the activation ratio between the genders (p>0.05). Conclusion: There were no gender-based differences in the activation ratio of vastus medialis oblique to vastus lateralis during weight-bearing and non-weight-bearing activities. Keywords: Quadriceps muscle, Patellofemoral pain, Sex factors, Weight, Electromyography.